(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
In the past, selling goods and services was the focal point of every business industry. The transition of time has proven that Corporate Social responsibility is equally important. Corporate social responsibility (CSR) is a self-policing corporate strategy that enables an organization to be socially accountable to its customers, employees, and stakeholders. It has then become a new model of modern business competition. The Hospitality Industry is no different. The hospitality industry was and has always been a customer-oriented business. Such services include cleanliness, comfort, VIP treatment, and health priority to all stakeholders, customers, and the environment. During the pandemic COVID-19, however, businesses were racked, global finances dwindled, and customer loyalty was greatly diminished. Survivability was then a priority. The situation above demonstrates the struggle of every business. Has the pandemic brought the ultimate catastrophe, or should there be a lesson to learn from? The objective of this study is to analyze the effects of the pandemic on businesses, especially the hospitality industry for future business strategy. The researcher used a combination of two methods. First, studying different literature. Different works of literature were already published at this point and the researcher was able to compile thoughts from different authors. By studying different research, the researcher was able to clarify some variables related to this study. Multiple case-study research was also studied. The second is the descriptive research design which intends to describe facts and clarify some issues. By using the said research design, the researcher was able to conceptualize the focus of this study. "How does corporate social reasonability connect with customer satisfaction? According to Khawaja, Ali, & Mostapha (2021), there is a relationship between corporate social responsibilities, service quality, customer satisfaction, brand loyalty, and customer perceived value. Customer satisfaction is the result of service quality, customer perceived value, and brand loyalty. How does CSR contribute to customer satisfaction during the pandemic? The other side of experience in the pandemic has opened opportunities for re-evaluation and planning. While businesses were suffering from rising unemployment, losing profit, low productivity, looming household expenditures, psychological fatigue, and loss of product values. CSR must recover positive brand images through policies that would address health issues, restore product values, financial statements, strengthen employment conditions, and restructure the supply chain. In return, these will reflect stakeholders’ satisfaction. What is corporate social responsibility in the hospitality industry? Throughout the onset of pandemic COVID-19, hotel employees became resilient, more cooperative, and proactive, and considered partners in managing the pandemic. Also, CSR has a very important role in promoting employee safety, upholding employee morale, and helping improve future hotel development and strategies. What are the challenges of the pandemic in hospitality marketing? Thus, the travel restrictions and the reluctant visitors contributed to the decline in hospitality industry profitability. Nonetheless, the study also showed that aside from safety reasons, customers were also more loyal to establishments with high regard for corporate social responsibility. According to Qiu, et al. (2021), preserving the hospitality firm’s value was paramount. CSR has a very important role to sustain hospitality market performance and its value to employees, customers, stakeholders, and the communities. CSR was necessary to maintain the company’s image, retain customers’ brand loyalty, and preserve a safe and healthy environment. In the hospitality industry, CSR during the pandemic remained constant; It was the continuous commitment of every hospitality establishment to maintain a safe and healthy environment, according to Abram & Jarząbek (2016), CSR in the hospitality industry includes ensuring the health and safety of all employees and the guests and reducing unhealthy effects in the environment and respecting the cultural values of the company and the community. The sustainable development goal (SDG) of the hospitality industry forms a major part of the CSR such as the integration of local cultural values into hospitality visions is an additional experience for all forms of stakeholders. These principles and practices can be applied in the marketing strategies of the industry, for it was always the goal of the hospitality industry to provide safe, healthy services along with comfort, these will attract quality-conscious customers. loyalty (Khawaja, Ali, & Mostapha, 2021); the pandemic has opened opportunities for re-evaluation and planning; CSR strategies employed in the pandemic setting resulted in hotel employees’ resilience, cooperation, and proactiveness. Employees also became partners in pandemic management. Further, CSR was integral in upholding employee safety and morale and improving future hotel development and strategies.